Regulation of the translocation efficiency of Icm/Dot translocated substrates by protein conformation. - Amyot, Whitney. (2017)
Abstract: Legionella pneumophila uses a type 4B secretion system known as the Icm/Dot system to deliver over 200 effector proteins to the host cell for the establishment and maintenance of a replication vacuole. Translocation of a large majority of these Icm/Dot translocated substrates (IDTS) is facilitated by the Icm/Dot adapter complex IcmS/W. The characteristics of translocation competence for substrates of the Icm/Dot secretion system are poorly elucidated. In these studies, I investigated the effect of protein conformation on Icm/Dot translocation efficiency by analyzing the translocation of stably folded IDTS fusions and the interaction of IDTS with the chaperone protein complex IcmS/W. IDTS fused to dihydrofolate reductase (DHFR) or to folded ubiquitin (Ub) exhibited a kinetic defect in translocation, indicating that substrates of the Icm/Dot T4SS are translocated to the host cytosol in an extended or unfolded conformation. Additionally, expression of folded substrates decreased the translocation of at least one IDTS, suggesting that these proteins are blocking the translocon or impairing the function of the Icm/Dot complex. The requirement of IcmS/W for translocation of IDTS was also characterized as a kinetic response that varied between IDTS, suggesting a role of IcmS/W in the temporal regulation of translocation. Deletion analysis of the IDTS MavU and SidG failed to identify a specific site for IcmS/W binding. Rather, IcmS/W interacted with multiple regions within the IDTS as well as the enzymatic domain of CyaA, the adenylate cyclase toxin of Bordetella pertussis. IcmS/W also facilitates the transport or recognition of folded proteins, as DHFR fusions exhibit a severe translocation defect in an icmS- mutant strain. These data are consistent with a role for IcmS in promoting translocation efficiency by non-specifically binding to proteins to hold them in an elongated or partially unfolded conformation for recognition by the Icm/Dot complex.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Ralph Isberg.; Committee: Carol Kumamoto, Abraham Sonenshein, Joan Mecsas, and Joseph Vogel.; Keyword: Microbiology.